Environmental and Economic Impacts of the National Energy and Climate Plan of Cyprus - Zachariadis, Theodoros; Taliotis, Constantinos; Fylaktos, Nestor; Karmellos, Marios; Giannakis, Elias; Andreou, Sofia N. (My University, 2020)
This paper provides a summary of the Impact Assessment of the National Energy and Climate Plan of Cyprus, which was submitted by the Cypriot government to the European Commission in January 2020. The analysis is based on detailed modelling of the national energy system in combination with simulations by macroeconomic and household demand models. The study has produced numerous results describing the energy, environmental and economic impacts of different scenarios. This paper focuses on some key findings and recommendations that are of interest to economic policy makers. Results show that the planned energy and climate policies of the Cypriot government, while contributing to compliance of Cyprus with its legally binding energy and environmental obligations, can also yield economic benefits to society. However, they require strong political will to implement, and this especially applies to measures promoting sustainable transport. As further decarbonisation measures will be needed in the coming years, the country can exploit business and investment opportunities arising from the global energy transition.
Keywords: Decarbonisation; Emissions Abatement; Greenhouse Gases; Input-Output Model; Renewable Energy